NILAI DAN ETIKA GENERASI Z SEBAGAI DIGITAL NATIVES DI ERA KERJA DIGITAL: SYSTEMATIC LITERATURE REVIEW - Regina Shafa An Najmah; Putri Diahayu Pitaloka; Masita; Lely Nur Azizah; Ni Wayan Sukmawati Puspitadewi (CV. ADIBA AISHA AMIRA, 2026)
Generation Z, as digital natives who have grown up in a fully digital environment, faces a gap between ideal expectations regarding technological proficiency and the reality of ethical understanding and work values in the digital era. This study aims to systematically examine the characteristics of work values, professional ethical attitudes, and factors influencing the formation of Generation Z's values and ethics in the context of digital work. The method used is a Systematic Literature Review (SLR) following the PRISMA protocol, searching for articles in the Google Scholar database from 2021 to 2026. Out of 114 initial articles, only 5 met the inclusion criteria for analysis. The review findings indicate that Generation Z's work values are not globally homogeneous but are influenced by national cultural contexts. Generation Z has a strong affinity with technology and prioritizes access to modern digital tools and automation, yet shows diverse preferences regarding work flexibility. Another key finding is that digital competence alone is insufficient to improve performance without being balanced by a strong work ethic; work ethics act as a mediator between digital competence and performance, as well as influencing work motivation and job satisfaction. This study concludes that optimizing Generation Z's potential in the digital work era requires the simultaneous integration of strengthening digital competence and fostering professional ethical values.